The Effect of Dialectical Behavior Therapy on Negative Automatic Thoughts, Suicidal Ideation and Life Expectancy in Female Students of Yasooj University of Medical Sciences - Rahimi, Elham; Maredpour , Alireza (Shahroud Journal of Medical Sciences, 2021)
Background: Suicide has occurred in all cultures and eras is a disaster for the individual, family, and society. Dialectical behavior therapy is a practical treatment for major depressive disorder. The main aim of the present study was to investigate the effect of dialectical behavior therapy on negative automatic thoughts, suicidal ideation, and life expectancy in female students of Yasooj University of Medical Sciences.Methods: The research method is quasi-experimental and the statistical population of the study included female students of Yasooj University of Medical Sciences in the age range of 18 to 25 years. The sample size was 40 people who were selected by a convenience sampling method and were randomly divided into two groups of dialectical behavior therapy and control group. To collect data, Snyder Hope Scale, Negative Automatic Thought Scale, and Beck Suicidal ideation Questionnaire in pre-test and post-test stages were used. In the intervention phase, the experimental group underwent dialectical behavior therapy for ten sessions of 120 minutes while the control group did not receive any intervention during this period. Data analysis was performed using SPSS software.Results: The findings indicate that dialectical behavior therapy was effective in increasing life expectancy and reducing negative automatic thoughts (Pvalue=0.001) and was not significantly effective in reducing suicidal ideation.Conclusions: Considering the effectiveness of dialectical behavior therapy on reducing negative thoughts and increasing the level of hope, therefore dialectical behavior therapy training is recommended to increase knowledge and empower students against depression and its components.Keywords: Dialectical behavior therapy, Suicidal ideations, Negative automatic thoughts, Life expectancy